2008
DOI: 10.1038/sc.2008.139
|View full text |Cite
|
Sign up to set email alerts
|

Manual wheelchair stroke characteristics during an extended period of propulsion

Abstract: Methods: Kinetic data were recorded from 21 subjects with paraplegia at four time points over the course of a 10-min propulsion trial at a steady state speed of 1.4 m s À1 . Upper extremity kinetic parameters were recorded using Smartwheels, force and torque sensing pushrims. Results: Subjects for propulsion biomechanics changed from early to late during the 10-min trial. Individuals displayed decreased maximum rate of rise of resultant force (P ¼ 0.0045) with a simultaneous increase in push time (P ¼ 0.043) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
2
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 15 publications
(22 reference statements)
0
21
2
2
Order By: Relevance
“…Rice et al reported an increase in push time during an extended period of propulsion, while stroke frequency remained static [42]. In the present study, no significant effects of kinetic variables on the endurance time of wheelchair propulsion were found.…”
Section: Effect Of Muscle Fatigue On Wheelchair Kineticscontrasting
confidence: 44%
“…Rice et al reported an increase in push time during an extended period of propulsion, while stroke frequency remained static [42]. In the present study, no significant effects of kinetic variables on the endurance time of wheelchair propulsion were found.…”
Section: Effect Of Muscle Fatigue On Wheelchair Kineticscontrasting
confidence: 44%
“…These studies found lower cadences increased mechanical efficiency and reduced self-reported perceived exertion measures, suggesting that lower demand is placed on the upper extremity (Goosey-Tolfrey and Kirk, 2003; Lenton et al, 2009). To our knowledge, only one study has investigated how altering contact angle influences wheelchair mechanics (using a single subject), but did not analyse specific measures of upper extremity demand (Rice et al, 2009). Potential reasons for the lack of studies may be due to the extreme difficulty in obtaining specific measures of upper extremity demand (e.g., muscle stress) or that longitudinal intervention studies can be confounded by other influences (e.g., physiological adaptation).…”
Section: Introductionmentioning
confidence: 99%
“…In another study by Rice et al, 11 experienced users pushing for an extended period tended to propel with longer stroke lengths and reduced forces toward the end of a 10-min trial vs. at start-up. Many of these subjects were very experienced and seemed to place an emphasis on push efficiency and energy conservation toward the end of the extended trial.…”
Section: Propulsion Trainingmentioning
confidence: 94%